Colonialities And Cartographic Disputes In Traditional Territories On The Southeast-South Coast Of Brazil - Erica Vicente Onofre; Flávia Rossato; Carina Catiana Foppa (Ambiente & Sociedade)
Abstract The field of classical cartography has historically been mobilised to produce maps that serve as mechanisms for controlling and conquering territories. In opposition to this logic, the critical cartography movement suggests incorporating a diversity of interpretations and worldviews into territory representations. This article discusses the processes of cartographic elaboration within the scope of academic research in the context of traditionally occupied territories on the coast of the Brazilian states of Paraná and São Paulo, which are overlapped by development projects and Conservation Units. These cartographies allow the problematisation of overlaps involving the territories of the Guarani Indigenous people and traditional artisanal fishing communities by considering the autocartography of these social groups to produce counter-information in the face of the erasure of subjectivities and territorialities embedded in the instruments associated with environmental and land-use planning policies.